Representasi Nilai Kearifan Lokal pada Pantun Melayu Deli dan Pelestariannya Melalui Telangkai - Hajar, Ibnu; Indriyanto, Kristiawan; Syahfitri, Dian (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study examines the representation of local wisdom values in Deli Malay pantun, especially those used in traditional wedding ceremonies, as well as efforts to preserve them through the telangkai profession in North Sumatra. Using semiotics and structuralism theories, this study found local wisdom values in 18 pantuns that are preserved in each stanza. These pantuns reflect the principles of politeness and respect in social interaction, where the ethics of speaking with pantun becomes a symbol of respect between individuals and groups. Respect for culture is also evident in the spirit of preserving Malay customs to be remembered and passed on to the next generation. The symbolism of nature in pantun, such as the rambai tree and mango fruit, teaches people to appreciate time and process in life. This research also highlights the role of the telangkai profession as the guardian of Malay pantun preservation. As professional pantun speakers, telangkai play an important role in maintaining this oral tradition in traditional ceremonies. However, this profession faces great challenges due to the influence of mass media and popular culture. To survive, some telangkai in North Sumatra have started to adopt digital media to disseminate pantun and involve the younger generation in the preservation of this oral literature. Preservation efforts through training, workshops, and pantun competitions are also carried out by cultural communities to arouse public interest in Malay pantun.